PENINGKATAN KETERAMPILAN REKAYASA, MINAT TERHADAP SAINS DAN TEKNOLOGI, KOMUNIKASI ILMIAH SD MELALUI PEMBELAJARAN STEAM BERBASIS TEKNOLOGI - Dwi Kartini, - (2021)
STEAM learning has many benefits for students, especially in enhancing learning science, technology, engineering, arts and mathematics. Then, STEAM learning is the learning of the 21st century. STEAM learning is to prepare a reliable generation in science and technology. Many students were interested in learning STEAM. However, STEAM learning was still difficult because Indonesian students are not used to learning STEAM. This study aims to improve engineering skills, interest in science and technology and also to see the scientific communication skills of elementary school students. This research method used a quasi-experimental design method and the design used the nonequivalent control group design, the experimental group and the control group are not selected randomly. The sample was taken using the convenient sampling technique, that is, the sample was taken as is. The sample of this research was 60 students in grade 3 in Bandung. 30 students in the STEAM Class and 30 students in the Non STEAM Class. The results showed that there was an increase in engineering skills at the redesign stage. Interest in science and technology in the STEAM class has also increased better than in the Non STEAM class. Then, scientific communication especially in the oral presentation in the STEAM class showed better results compared to the Non STEAM class. The results of this study indicate that STEAM learning can improve engineering skills, interest in science and technology and can also train scientific communication on oral presentations.